2021
DOI: 10.3389/fcell.2021.643856
|View full text |Cite
|
Sign up to set email alerts
|

Functional Role of Class III Myosins in Hair Cells

Abstract: Cytoskeletal motors produce force and motion using the energy from ATP hydrolysis and function in a variety of mechanical roles in cells including muscle contraction, cargo transport, and cell division. Actin-based myosin motors have been shown to play crucial roles in the development and function of the stereocilia of auditory and vestibular inner ear hair cells. Hair cells can contain hundreds of stereocilia, which rely on myosin motors to elongate, organize, and stabilize their structure. Mutations in many … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 122 publications
(190 reference statements)
0
18
0
Order By: Relevance
“…We performed a detailed characterization of the motor properties of MYO3A with a deafness mutation (L697W) in the motor domain and investigated the impact of the mutation on actin protrusion length/dynamics. It is well established that MYO3A is able to localize to the tips of actin protrusions, including stereocilia, microvilli, and filopodia, as well as promote the formation and elongation of these protrusions ( Les Erickson et al., 2003 ; Schneider et al., 2006 ; Salles et al., 2009 ; Quintero et al., 2010 ; Ebrahim et al., 2016 ; Raval et al., 2016 ; Cirilo et al., 2021 ). Our previous results demonstrated that the L697W mutant was still able to tip localize; however, it had a significantly decreased ability to induce and maintain the lengths of actin protrusions ( Dantas et al., 2018 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We performed a detailed characterization of the motor properties of MYO3A with a deafness mutation (L697W) in the motor domain and investigated the impact of the mutation on actin protrusion length/dynamics. It is well established that MYO3A is able to localize to the tips of actin protrusions, including stereocilia, microvilli, and filopodia, as well as promote the formation and elongation of these protrusions ( Les Erickson et al., 2003 ; Schneider et al., 2006 ; Salles et al., 2009 ; Quintero et al., 2010 ; Ebrahim et al., 2016 ; Raval et al., 2016 ; Cirilo et al., 2021 ). Our previous results demonstrated that the L697W mutant was still able to tip localize; however, it had a significantly decreased ability to induce and maintain the lengths of actin protrusions ( Dantas et al., 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, MYO3A dimerization has not been investigated and there is no predicted coiled-coil in the tail domain. In addition, other factors may play a significant role in MYO3A translocation to the tips of protrusions, such as interactions of the tail domain with actin and/or the plasma membrane (see Merritt et al , 2012 ; Cirilo et al , 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…This gene belongs to the non-muscle class I myosins, a sub-class of the unconventional myosin protein family, one of the earliest associated with hearing loss in humans and mice. Indeed, several members of this family have already been correlated with autosomal dominant and autosomal recessive hearing loss [43]. Regarding MYO1E, variants of this gene have been associated with Familial Focal Segmental Glomerulosclerosis (MIM# 614131) [44], and so far, no direct associations with the hearing system have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, cardiac muscle and smooth muscle myosin was reported in studies conducted by Bailey and Cohen et al [5,6]. Myosins are typically composed of three domains, a conserved head located in the N-terminal that binds to actin filaments, a short neck as a binding site for myosin light chain, and a tail located in the C-terminal generally binding to the motor "cargo" to determine the functions of the motor [7,8]. Eukaryotes contain up to 35 myosin subfamilies based on an analysis of 2269 Myosin motor domains from 328 organisms [9].…”
Section: Introductionmentioning
confidence: 99%
“…MYH11 is proven to be a useful marker to define myoid cells in mouse testis [12]. For unconventional myosin, myosin 3 plays a key role in regulating stereocilia lengths required for normal hearing [8]. myosin 5 is essential in intracellular transport of organelles, mRNA and other cargo [13].…”
Section: Introductionmentioning
confidence: 99%